Therapeutic siRNA targeting PLIN2 ameliorates steatosis, inflammation, and fibrosis in steatotic liver disease models - Wang, Yao; Zhou, Jiaxin; Yang, Qi; Li, Xinmeng; Qiu, Yifu; Zhang, Yansong; Liu, Min; Zhu, Alan Jian (Journal of lipid research, 2024)
Metabolic dysfunction–associated steatotic liver disease (MASLD) is the most prevalent chronic liver disease worldwide. If left untreated, MASLD can progress from simple hepatic steatosis to metabolic dysfunction–associated steatohepatitis, which is characterized by inflammation and fibrosis. Current treatment options for MASLD remain limited, leaving substantial unmet medical needs for innovative therapeutic approaches. Here, we show that PLIN2, a lipid droplet protein inhibiting hepatic lipolysis, serves as a promising therapeutic target for MASLD. Hepatic PLIN2 levels were markedly elevated in multiple MASLD mouse models induced by diverse nutritional and genetic factors. The liver-specific deletion of Plin2 exhibited significant anti-MASLD effects in these models. To translate this discovery into a therapeutic application, we developed a GalNAc-siRNA conjugate with enhanced stabilization chemistry and validated its potent and sustained efficacy in suppressing Plin2 expression in mouse livers. This siRNA therapeutic, named GalNAc-siPlin2, was shown to be biosafe in mice. Treatment with GalNAc-siPlin2 for 6–8 weeks led to a decrease in hepatic triglyceride levels by approximately 60% in high-fat diet– and obesity-induced MASLD mouse models, accompanied with increased hepatic secretion of VLDL-triglyceride and enhanced thermogenesis in brown adipose tissues. Eight-week treatment with GalNAc-siPlin2 significantly improved hepatic steatosis, inflammation, and fibrosis in high-fat/high fructose–induced metabolic dysfunction–associated steatohepatitis models compared to control group. As a proof of concept, we developed a GalNAc-siRNA therapeutic targeting human PLIN2, which effectively suppressed hepatic PLIN2 expression and ameliorated MASLD in humanized PLIN2 knockin mice. Together, our results highlight the potential of GalNAc-siPLIN2 as a candidate MASLD therapeutic for clinical trials.